Sensor-based Irrigation Scheduling, Soil Physical Properties and Wheat Productivity under Different Organic Amendments. Issue 17 (25th September 2022) - Kumar, Tushar; Kahlon, M S
ABSTRACT: Sensor-based irrigation scheduling in field crops like wheat for achieving optimum yield with minimum use of water needs investigation under different amendment practices. The present study was thus conducted to investigate the effect of four irrigation regimes i.e., soil moisture indicator (red level of indication, SMI), tensiometer (35 k Pa), IW/Pan-E 0.9, and IW/Pan-E 0.6 in main plots and four organic amendments i.e., farm yard manure (FYM), rice straw mulch, hydrogel and without amendments in subplots on soil physical properties and wheat productivity. The field experiment was laid out in split plot design with three replications during rabi 2020–21 at Research Farm, Department of Soil Science, PAU, Ludhiana. The use of SMI shows promising results in respect of scheduling irrigation in wheat as similar biological yield with same amount of water was achieved as that observed for recommended practice i.e., IW/PAN-E = 0.9. The results further indicate that the use of amendments, particularly FYM, leads to reduction in soil bulk density by 4%, while the soil moisture content at field capacity and water-holding capacity by 14% and 9.3%. It is, thus, concluded that scheduling irrigation based on SMI along with FYM in wheat is a suitable practice for northwest India.